Integration of a Low Gas-Saturated Zone in Creating a 3D Model of the Medvezhye Field - Artem Shirjaev; Yuri Vaganov; Vitaliya Naumenko (Qubahan Academic Journal)
3D geological modeling is an integral part of reserves estimation and project documentation for the development of gas and oil fields. The developed 3D geological model of the Cenomanian productive complex including the low gas-saturated zone of the Medvezhye field represents a combination of data from the drilling of 350 wells, the structural features of the reservoir, permeability properties determined on cores, seismic surveys, and the results of geophysical well surveys. Based on examining the available well logs recorded in the Medvezhye field wells, the low gas-saturated zone is integrated into the construction of the 3D geological model of the Medvezhye field of the Cenomanian productive complex. A total of three models are constructed, and a 400*400*0.4 m grid is recommended for further hydrodynamic modeling. A comparison of the three grids suggests that a more detailed model delivers more thorough results, however, heavy models cannot be applied to hydrodynamic modeling. Resource estimations do not differ across the three grids significantly.